Definition and Scope of Islamic Educational Philosophy - Agil Husain Abdullah; Ferdinan Ferdinan; Bahaking Rama (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
In modern developments, Islamic education faces various challenges, ranging from the currents of globalization, the development of science and technology, to complex socio-cultural problems. This situation demands a paradigm of Islamic educational philosophy that can meet the needs of the times without losing its roots in the values ​​of revelation. Thus, an in-depth study of the definition and scope of Islamic educational philosophy is important to emphasize the identity of Islamic education and its relevance in forming a complete human being (insan kāmil). This study uses a qualitative approach with a library research type. The results of this study indicate that the critical and ethical scopes in Islamic educational philosophy complement each other and form a paradigmatic unity. The critical scope functions to dismantle assumptions that restrict human freedom of thought and creativity, the ethical scope provides normative direction so that this freedom does not deviate from human and divine values, and the scope of transformative orientation makes Islamic education an agent of social change.